Community perceptions of changes in rural livelihoods since onset of COVID-19 in Myanmar: Insights from Round 7 of the National COVID-19 Community Survey (NCCS) – May 2021 - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
COVID-19 prevention measures are at their lowest levels since June 2020. However, several restrictions were recently implemented to curtail political unrest that are likely to also slow the spread of the virus. Communities have experienced further reductions in employment opportunities. The estimated share of adults who are unemployed is at its highest level since June 2020. In May 2021, respondents estimated that nearly half of adults in urban communities and 37 percent of adults in rural communities were unemployed in the past month. Agricultural production thus far appears robust but has suffered from poor weather conditions, whereas crop sales are affected by low crop prices and mobility restrictions. The share of households receiving remittances is estimated to be only half of those receiving remittances at the end of 2020. Whereas the end of the year is traditionally a period where more remittances are received, the recent decline is likely also related to challenges in the financial sector and to reduction in domestic employment, especially in urban areas. Financial services are disrupted in two-thirds of the communities. These disruptions include bank closures (in 58 percent of communities), challenges in meeting loan officers (19 percent), and shortages of money in ATMs (7 percent). There is a stark increase in the share of households who urgently need assistance. Community respondents estimate that in May 2021 one-third of households on average are in urgent need of assistance, which is twice as high as the share estimated in July 2020. Coping mechanisms have changed since mid-2020 with communities no longer receiving cash-based assistance. Households are relying less on credit and loans. Instead, they are increasingly reducing both food and non-food expenditures and selling agricultural and non-agricultural assets.